HPA axis regulation in posttraumatic stress disorder: A meta-analysis focusing on potential moderators. (May 2019) - Schumacher, Sarah; Niemeyer, Helen; Engel, Sinha; Cwik, Jan Christopher; Laufer, Sebastian; Klusmann, Hannah; Knaevelsrud, Christine
Highlights: Overall, morning and 24 h cortisol was significantly lower in PTSD than controls (trauma-exposed and non-trauma exposed controls). No clear pattern of dysregulation was found across investigated moderators. Guidelines regarding standardized assessment of hormone parameters are needed. Abstract: Posttraumatic stress disorder (PTSD) is often associated with alterations in the hypothalamic–pituitary–adrenal (HPA) axis. Previous findings are inconsistent, possibly due to trauma exposure of controls or different hormone measurement methods. We investigated cortisol, dehydroepiandrosterone (DHEA) and its sulfate (DHEA-S) in adults with clinical PTSD under basal or challenged conditions (Prospero registration no. CRD42016041690 ). A search of PubMed, Scopus, Medline, PsycINFO, Pilots/ProQuest, and Web of Science resulted in 108 included studies ( N = 6484). Morning and 24 h cortisol were significantly lower in PTSD than in controls ( g = −0.21; 95% CI: −0.42–(−0.01); g = −0.31; CI: −0.60–(−0.03)). Significant cortisol increases occurred after awakening in PTSD ( g = 0.40; CI: 0.13–0.67) and in non-exposed controls ( g = 0.96; CI: 0.59–1.33). Evening DHEA was significantly higher in PTSD than in non-exposed controls ( g = 0.58; CI: 0.17–0.99). All groups showed large cortisol suppression effects after dexamethasone administration. Overall, the potential moderators investigated did not reveal a consistent pattern of HPA alterations.